A STUDY OF POLLUTION LOAD CAPACITY OF THE INDUSTRIAL SECTOR IN CIBABAT RIVER IN THE WATERSHED OF CITARUM RIVER - Mochammad Fariq Yogaswara; Iwan Juwana; Yenita Sandra Sari; Haroon Bakari (INDONESIAN JOURNAL OF URBAN AND ENVIRONMENTAL TECHNOLOGY, 2019)
The Sub Watershed of Cibabat is one of the rivers included in the Upstream Citarum River, in Cimahi City. This industrial sector which consists of 36 different industries is among the highest contributors of pollution load. Aim: This study analyzed the pollutant loads entering the Cibabat River in existing conditions and projections from the industrial sector. Methodology and Results:  The pollutant loads, emitted from the industrial sector was used to calculate the discharged data, concentration, number of employees and products, as well as emission factors (EF). In 2018, the industrial sector pollution load was 3,518.82 kg/day TSS, 8,231.83 kg/day BOD and 14,467.68 kg/day COD. However, it increased to 3,885.06 kg/day TSS, 9,088.61 kg/day BOD and 15,973.48 kg/day COD during this project year. Conclusion, significance and impact study: The pollution loads on Cibabat River emitted from the industrial sector, which increases yearly by 2% was be reduced by developing wastewater treatment communal for industries.